A bipolar membrane containing a Ti3C2@TiO2 catalytic interlayer and a preparation method and application thereof

CN122999007APending Publication Date: 2026-10-30ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610956709.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

一方面,Ti3C2在潮湿、高温环境下易发生氧化变质,大幅削弱催化性能、缩短使用寿命,而双极膜工作体系的酸碱环境,进一步加剧了其稳定性难题;另一方面,Ti3C2纳米片间存在较强的范德华力与静电相互作用,极易发生团聚堆叠,造成材料比表面积缩减、活性反应位点流失,最终不利于膜体系内的离子传输与水解离催化效率

Benefits of technology

[0017]本申请先采用氟化锂-盐酸刻蚀体系制备层状Ti3C2@TiO2,再通过酸性水热工艺在Ti3C2Tx纳米片表面原位生长TiO2纳米颗粒,得到Ti3C2@TiO2复合催化材料;将该复合催化剂通过浸渍法负载于阴离子交换膜界面构筑催化中间层,再流延涂布磺化聚醚醚酮铸膜液,经分段交联、NaCl溶液活化后得到三层夹层结构改性双极膜,并通过调控催化剂浸渍浓度筛选最优改性样品。相较于现有单一Ti3C2或TiO2改性双极膜,本申请具备如下优势:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999007A_ABST
    Figure CN122999007A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of ion exchange membranes, and particularly relates to a bipolar membrane containing a Ti3C2@TiO2 catalytic intermediate layer and a preparation method and application thereof. x The Ti3C2@TiO2 composite catalyst is loaded on the interface of an anion exchange membrane by an immersion method to construct a catalytic intermediate layer, a sulfonated polyether ether ketone casting solution is coated by flow casting, and after being subjected to segmented crosslinking and NaCl solution activation, a three-layer sandwich structure modified bipolar membrane is obtained, and the optimal modified sample is selected by regulating and controlling the catalyst immersion concentration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of ion exchange membrane technology, specifically relating to a bipolar membrane containing a Ti3C2@TiO2 catalytic intermediate layer. Background Technology

[0002] A bipolar membrane is a special type of composite ion exchange membrane, mainly composed of a cation exchange layer, an anion exchange layer, and a hydrophilic interface layer between the two layers. Water treatment processes using a bipolar membrane as the core component are called bipolar membrane electrodialysis. Under the drive of an applied DC electric field, water molecules dissociate at the hydrophilic interface layer of the bipolar membrane, generating H+. + and OH - ;where H + OH migrates to the cathode through the cation exchange layer. - The ions migrate through the anion exchange layer to the anode and accumulate in different chambers, thus generating acid and alkali solutions in situ. Based on this unique in-situ acid and alkali production characteristic, bipolar membrane electrodialysis technology can be widely used in many fields such as acid and alkali preparation, carbon dioxide removal, amino acid and organic matter regeneration, desulfurizing agent regeneration, and alcohol decomposition.

[0003] According to chemical reaction model theory, the chemical composition and molecular structure of the hydrophilic interfacial catalyst are the core factors determining the water dissociation performance of bipolar films. Catalysts immobilized within the interfacial layer can construct alternative reaction pathways, effectively lowering the activation energy threshold of the water dissociation reaction, increasing the reaction rate, and reducing the system overpotential. Therefore, scholars both domestically and internationally have conducted extensive research on bipolar film water dissociation catalysts. Traditional research subjects mainly include organic polymers such as polyvinyl alcohol, polyethylene glycol, 2,6-pyridine dicarboxylic acid, and poly(4-vinylpyridine), as well as inorganic compounds such as molybdenum disulfide and potassium ferrocyanide. In recent years, two-dimensional materials such as carbon-based materials, graphene oxide, and MXenes have become new research hotspots in the field of bipolar film catalysts due to their excellent performance. Among them, the general molecular formula of MXenes is M... n+1 X n T x It is mainly prepared by acid etching of ternary layered compounds, where M represents early transition metals such as titanium, zirconium, hafnium, vanadium, and niobium, X is carbon or nitrogen, and T is... x These correspond to functional groups such as -F, -Cl, -OH, and -O on the surface of the material.

[0004] Existing research confirms that Ti3C2 is a high-performance water dissociation catalytic material, but its practical application still has significant shortcomings. On the one hand, Ti3C2 is prone to oxidation and deterioration in humid and high-temperature environments, which significantly weakens its catalytic performance and shortens its service life. The acidic and alkaline environment of the bipolar membrane working system further exacerbates its stability problem. On the other hand, the strong van der Waals forces and electrostatic interactions between Ti3C2 nanosheets make them prone to aggregation and stacking, resulting in a reduction in the material's specific surface area and loss of active reaction sites, ultimately hindering ion transport and water dissociation catalytic efficiency within the membrane system. Summary of the Invention

[0005] The purpose of this application is to provide a bipolar membrane with high catalytic efficiency and better catalytic performance, which is achieved through the following technical solution:

[0006] A method for preparing a bipolar film containing a Ti3C2@TiO2 catalytic interlayer includes the following steps: Ti3C2T x Sodium fluoroborate and hydrochloric acid undergo a hydrothermal reaction at 150~170℃ to obtain Ti3C2@TiO2; Ti3C2@TiO2 is loaded onto an anion exchange base membrane as a carrier and dried to form a Ti3C2@TiO2 catalytic intermediate layer; a cation exchange precursor membrane is formed by casting a cation exchange membrane onto the surface of the Ti3C2@TiO2 catalytic intermediate layer.

[0007] Preferably, the Ti3C2T x The preparation method includes the following steps: treating titanium aluminum carbide with lithium fluoride-hydrochloric acid etching to obtain Ti3C2T. x .

[0008] As a preferred method, after forming the cation exchange precursor membrane, it is subjected to segmented high-temperature cross-linking and curing: the first cross-linking temperature is 70-90℃, the second cross-linking temperature is 90-110℃, and after the cross-linking is completed, a composite bipolar membrane semi-finished product is obtained.

[0009] Preferably, the method further includes immersing the composite bipolar membrane semi-finished product in a 0.2~0.8 mol / L NaCl solution for activation treatment to obtain the bipolar membrane.

[0010] Preferably, the raw material ratio in step S1 is: 180-220 mg Ti3C2T x The powder corresponds to 25–35 mL of a mixture of 0.8–1.2 mol / L hydrochloric acid containing 0.15–0.25 mol / L sodium fluoroborate.

[0011] Preferably, the cation-coating solution is an organic solution of sulfonated polyether ether ketone, wherein the solid content of the sulfonated polyether ether ketone is 8-12 wt%.

[0012] As a preferred embodiment, the preparation process of the sulfonated polyether ether ketone is as follows: polyether ether ketone is dissolved in concentrated sulfuric acid for sulfonation reaction; after the reaction is completed, the mixture is poured into ice water to quench and terminate the reaction, and a white flocculent crude sulfonated polyether ether ketone product is precipitated; the crude sulfonated polyether ether ketone product is washed with deionized water and vacuum dried to obtain sulfonated polyether ether ketone.

[0013] Preferably, the method includes the following steps: loading Ti3C2@TiO2 onto the surface of anion exchange base membrane using an impregnation method.

[0014] A bipolar membrane containing a Ti3C2@TiO2 catalytic intermediate layer is prepared by any of the preparation methods described above.

[0015] The above-mentioned application of a bipolar membrane containing a Ti3C2@TiO2 catalytic intermediate layer in electrodialysis.

[0016] Compared with the prior art, this application has the following beneficial effects:

[0017] This application first uses a lithium fluoride-hydrochloric acid etching system to prepare layered Ti3C2@TiO2, and then uses an acidic hydrothermal process to etch Ti3C2@TiO2. x TiO2 nanoparticles were grown in situ on the surface of nanosheets to obtain a Ti3C2@TiO2 composite catalytic material. This composite catalyst was loaded onto the interface of an anion exchange membrane using an impregnation method to construct a catalytic intermediate layer. Sulfonated polyetheretherketone (PEEK) casting solution was then cast and coated, followed by segmented crosslinking and activation with NaCl solution to obtain a three-layer sandwich structure modified bipolar membrane. The optimal modified sample was screened by controlling the catalyst impregnation concentration. Compared with existing single Ti3C2 or TiO2 modified bipolar membranes, this application has the following advantages:

[0018] The Ti3C2@TiO2 composite catalytic interlayer synergistically enhances water dissociation catalytic activity and long-term service stability. Layered Ti3C2T x With excellent electrical and hydrophilic properties, it can construct continuous and rapid ion transport channels at the membrane interface; the in-situ grown TiO2 nanoparticles can provide abundant Lewis acid catalytic sites, while preventing the stacking and aggregation of Ti3C2 nanosheets, thus avoiding their oxidation and deactivation under acid and alkaline conditions. The synergistic effect of the two phases significantly reduces the activation energy of water dissociation reaction and accelerates the interfacial water decomposition kinetics.

[0019] Electrochemical IV performance tests confirmed that the Ti3C2@TiO2 catalytic interlayer significantly reduced the bipolar membrane transmembrane voltage and water dissociation initiation potential. The Ti3C2@TiO2-0.25 BPM catalyst with an impregnation concentration of 0.25 g / L exhibited the best overall performance at 100 mA·cm⁻¹. -2At the current density, the transmembrane voltage was only 1.75V, a 37.3% reduction compared to the blank bipolar membrane (2.79V) without a catalytic interlayer; the water dissociation initiation voltage decreased from 0.98V in the blank membrane to 0.85V, a reduction of 13.3%. Results from experiments with different catalyst loading gradients showed that the transmembrane voltage of each modified bipolar membrane decreased by 14.3% to 37.3% relative to the blank membrane.

[0020] Long-term stability tests with constant current demonstrate a significant improvement in the long-term performance of the bipolar membrane of this invention. (At 100 mA·cm⁻¹) -2 After 6 hours of continuous operation under constant current, the transmembrane voltage of the blank bipolar membrane continued to increase, with a rise rate of 44.5 mV·h. -1 The voltage of the Ti3C2@TiO2 modified bipolar membrane showed no significant fluctuation. The in-situ composite structure can firmly anchor the catalyst material to the membrane interface, effectively inhibiting catalyst dissolution and shedding, and ensuring stable water dissociation efficiency under long-term electrolysis conditions.

[0021] In summary, this application utilizes an in-situ composite Ti3C2 and TiO2 interfacial catalysis strategy to simultaneously address the shortcomings of traditional MXene catalytic materials, such as easy oxidation, aggregation, and loss, as well as the slow water dissociation kinetics, high operating energy consumption, and poor stability of bipolar membranes. This provides a complete and feasible preparation route for the preparation of efficient and long-life bipolar membranes for electrodialysis. Attached Figure Description

[0022] The attached diagram will be briefly described below:

[0023] Figure 1 This is a process route diagram for the fabrication of bipolar films;

[0024] Figure 2 (a) shows Ti3C2T after HF etching. x The morphological image shows that it exhibits a typical accordion-like structure, which is completely consistent with the literature reports, indicating that Ti3C2T x (a) shows the successful preparation of TiO2; (b) shows that TiO2 particles have been successfully grown on the surface of Ti3C2 nanosheets, with a large specific surface area and many water dissociation catalytic sites; (c) shows the XRD pattern of the prepared sample Ti3C2@TiO2; (d) shows the elemental surface distribution analysis results of the prepared Ti3C2@TiO2 material, which shows that C, O and Ti elements are uniformly distributed on the material surface.

[0025] Figure 3(a) is a low-magnification SEM image of the bipolar membrane cross section, showing a regular sandwich three-layer structure with a sulfonated polyether ether ketone cation membrane layer thickness of approximately 104 μm; (b) is a magnified SEM image of the membrane interlayer interface, showing that the cation and cation membranes are tightly bonded to the catalytic intermediate layer without obvious gaps; (c) is an EDS elemental surface scan of the bipolar membrane cross section, showing that C, O, and S elements are evenly distributed in layers, clearly distinguishing the cation and cation membrane regions, confirming the successful construction of the sandwich structure.

[0026] Figure 4 In the middle, (a) and (b) are the IV curves of blank bipolar film, pure Ti3C2, pure TiO2 and Ti3C2@TiO2-0.25 modified bipolar film, and (c) and (d) are the IV curves of Ti3C2@TiO2 modified bipolar film with different impregnation concentrations.

[0027] Figure 5 (a) Schematic diagram of the BMED device used for acid and alkali production and (b) bipolar membrane at 100 mA / cm². -2 Cyclic stability curves at current densities. Detailed Implementation

[0028] The present application will now be further described by way of specific embodiments. Those skilled in the art will be able to implement the present application based on these descriptions. Furthermore, the embodiments of the present application described below are generally only a part of the embodiments of the present application, and not all of the embodiments. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present application without inventive effort should fall within the scope of protection of the present application.

[0029] Example 1

[0030] This embodiment discloses a method for preparing a bipolar film containing a Ti3C2@TiO2 catalytic interlayer, specifically including the following steps:

[0031] 1. Ti3C2T x Preparation

[0032] Ti3C2T was prepared by etching Ti3AlC2MAX using a lithium fluoride-hydrochloric acid etching method. xMaterials. First, 1.88 g of lithium fluoride (LiF) powder was added to 30 mL of 9 M hydrochloric acid (HCl) solution and stirred. Then, 2 g of titanium aluminum carbide (Ti3AlC2MAX) precursor powder was slowly added at room temperature for 30 min. The mixture was then stirred for 48 h to allow for complete reaction. The resulting solution was diluted with deionized water, placed in centrifuge tubes, and centrifuged at 9000 rpm for 10 min to remove the precipitate. This process was repeated several times until the pH of the supernatant after centrifugation was measured to be 7 using pH paper. The resulting MXene sample was dried in a vacuum oven at 65 °C and then stored in a dark, oxygen-free environment.

[0033] 2. Preparation of Ti3C2@TiO2

[0034] 200mg Ti3C2T x Add 0.2M NaBF4 to 30mL of 1.0M HCl. After mixing and stirring the solution for 30min, transfer it to a 100mL stainless steel autoclave lined with polytetrafluoroethylene and hydrothermally heat it at 160℃ for 12h. After naturally cooling to room temperature, centrifuge, wash several times with deionized water, and dry in a vacuum drying oven at 60℃ for 12h.

[0035] 3. Preparation of sulfonated polyetheretherketone cation exchange solution

[0036] 4g of peek was dried under vacuum at 100℃ for 24 hours. The dried sample was then dissolved in 100mL (80-150mL) of concentrated sulfuric acid and stirred at 60℃ (50-70℃) for 5-8 hours until completely dissolved. The reaction was then stopped, and the product was slowly poured into 500mL of prepared ice water while stirring. A white flocculent product was obtained. The product was washed with deionized water until the pH was approximately 7. The product was then dried under vacuum at 100℃ (60-100℃) for 24 hours (24-36 hours) to obtain sulfonated polyether ether ketone. 1g of sulfonated polyether ether ketone was dissolved in 10mL of LDM to prepare a 10wt% solution.

[0037] 4. Preparation of bipolar films

[0038] Cut the purchased anion exchange membrane into 4cm x 4cm squares and thoroughly wet the base membrane. Place the anion exchange membrane on a membrane holder and dry the membrane. Load 1 mL of 0.1 g / L catalyst onto the base membrane (3.14 cm²) using an impregnation method. 2 As an intermediate layer, it is dried at 60℃ for 1 hour; on the side impregnated with the intermediate layer catalyst, a cation exchange film solution is cast and left to dry overnight under natural conditions to form a film. The next day, it is crosslinked at 80℃ for 2 hours and then at 100℃ for 1 hour. After complete drying, the prepared bipolar film is immersed in a 0.5 mol / L NaCl solution for 24 hours.

[0039] Example 2

[0040] This embodiment discloses a method for preparing a bipolar film containing a Ti3C2@TiO2 catalytic interlayer, specifically including the following steps:

[0041] 1. Ti3C2T x Preparation

[0042] Ti3C2T was prepared by etching Ti3AlC2MAX using a lithium fluoride-hydrochloric acid etching method. x Materials. First, 1.88 g of lithium fluoride (LiF) powder was added to 30 mL of 9 M hydrochloric acid (HCl) solution and stirred. Then, 2 g of titanium aluminum carbide (Ti3AlC2MAX) precursor powder was slowly added at room temperature for 30 min. The mixture was then stirred for 48 h to allow for complete reaction. The resulting solution was diluted with deionized water, placed in centrifuge tubes, and centrifuged at 9000 rpm for 10 min to remove the precipitate. This process was repeated several times until the pH of the supernatant after centrifugation was measured to be 7 using pH paper. The resulting MXene sample was dried in a vacuum oven at 65 °C and then stored in a dark, oxygen-free environment.

[0043] 2. Preparation of Ti3C2@TiO2

[0044] 200mg Ti3C2T x Add 0.2M NaBF4 to 30mL of 1.0M HCl. After mixing and stirring the solution for 30min, transfer it to a 100mL stainless steel autoclave lined with polytetrafluoroethylene and hydrothermally heat it at 160℃ for 12h. After naturally cooling to room temperature, centrifuge, wash several times with deionized water, and dry in a vacuum drying oven at 60℃ for 12h.

[0045] 3. Preparation of sulfonated polyetheretherketone cation exchange solution

[0046] 4g of peek was dried under vacuum at 100℃ for 24 hours. The dried sample was then dissolved in 100mL (80-150mL) of concentrated sulfuric acid and stirred at 60℃ (50-70℃) for 5-8 hours until completely dissolved. The reaction was then stopped, and the product was slowly poured into 500mL of prepared ice water while stirring. A white flocculent product was obtained. The product was washed with deionized water until the pH was approximately 7. The product was then dried under vacuum at 100℃ (60-100℃) for 24 hours (24-36 hours) to obtain sulfonated polyether ether ketone. 1g of sulfonated polyether ether ketone was dissolved in 10mL of LDM to prepare a 10wt% solution.

[0047] 4. Preparation of bipolar films

[0048] Cut the purchased anion exchange membrane into 4cm x 4cm squares and thoroughly wet the base membrane. Place the anion exchange membrane on a membrane holder and dry the membrane. Load 1 mL of 0.2 g / L catalyst onto the base membrane (3.14 cm²) using an impregnation method. 2 As an intermediate layer, it is dried at 60℃ for 1 hour; on the side impregnated with the intermediate layer catalyst, a cation exchange film solution is cast and left to dry overnight under natural conditions to form a film. The next day, it is crosslinked at 80℃ for 2 hours and then at 100℃ for 1 hour. After complete drying, the prepared bipolar film is immersed in a 0.5 mol / L NaCl solution for 24 hours.

[0049] Example 3

[0050] This embodiment discloses a method for preparing a bipolar film containing a Ti3C2@TiO2 catalytic interlayer, specifically including the following steps:

[0051] 1. Ti3C2T x Preparation

[0052] Ti3C2T was prepared by etching Ti3AlC2MAX using a lithium fluoride-hydrochloric acid etching method. x Materials. First, 1.88 g of lithium fluoride (LiF) powder was added to 30 mL of 9 M hydrochloric acid (HCl) solution and stirred. Then, 2 g of titanium aluminum carbide (Ti3AlC2MAX) precursor powder was slowly added at room temperature for 30 min. The mixture was then stirred for 48 h to allow for complete reaction. The resulting solution was diluted with deionized water, placed in centrifuge tubes, and centrifuged at 9000 rpm for 10 min to remove the precipitate. This process was repeated several times until the pH of the supernatant after centrifugation was measured to be 7 using pH paper. The resulting MXene sample was dried in a vacuum oven at 65 °C and then stored in a dark, oxygen-free environment.

[0053] 2. Preparation of Ti3C2@TiO2

[0054] 200mg Ti3C2T x Add 0.2M NaBF4 to 30mL of 1.0M HCl. After mixing and stirring the solution for 30min, transfer it to a 100mL stainless steel autoclave lined with polytetrafluoroethylene and hydrothermally heat it at 160℃ for 12h. After naturally cooling to room temperature, centrifuge, wash several times with deionized water, and dry in a vacuum drying oven at 60℃ for 12h.

[0055] 3. Preparation of sulfonated polyetheretherketone cation exchange solution

[0056] 4g of peek was dried under vacuum at 100℃ for 24 hours. The dried sample was then dissolved in 100mL (80-150mL) of concentrated sulfuric acid and stirred at 60℃ (50-70℃) for 5-8 hours until completely dissolved. The reaction was then stopped, and the product was slowly poured into 500mL of prepared ice water while stirring. A white flocculent product was obtained. The product was washed with deionized water until the pH was approximately 7. The product was then dried under vacuum at 100℃ (60-100℃) for 24 hours (24-36 hours) to obtain sulfonated polyether ether ketone. 1g of sulfonated polyether ether ketone was dissolved in 10mL of LDM to prepare a 10wt% solution.

[0057] 4. Preparation of bipolar films

[0058] Cut the purchased anion exchange membrane into 4cm x 4cm squares and thoroughly wet the base membrane. Place the anion exchange membrane on a membrane holder and dry the membrane. Load 1 mL of 0.25 g / L catalyst onto the base membrane (3.14 cm²) using an impregnation method. 2 As an intermediate layer, it is dried at 60℃ for 1 hour; on the side impregnated with the intermediate layer catalyst, a cation exchange film solution is cast and left to dry overnight under natural conditions to form a film. The next day, it is crosslinked at 80℃ for 2 hours and then at 100℃ for 1 hour. After complete drying, the prepared bipolar film is immersed in a 0.5 mol / L NaCl solution for 24 hours.

[0059] Example 4

[0060] This embodiment discloses a method for preparing a bipolar film containing a Ti3C2@TiO2 catalytic interlayer, specifically including the following steps:

[0061] 1. Ti3C2T x Preparation

[0062] Ti3C2T was prepared by etching Ti3AlC2MAX using a lithium fluoride-hydrochloric acid etching method. x Materials. First, 1.88 g of lithium fluoride (LiF) powder was added to 30 mL of 9 M hydrochloric acid (HCl) solution and stirred. Then, 2 g of titanium aluminum carbide (Ti3AlC2MAX) precursor powder was slowly added at room temperature for 30 min. The mixture was then stirred for 48 h to allow for complete reaction. The resulting solution was diluted with deionized water, placed in centrifuge tubes, and centrifuged at 9000 rpm for 10 min to remove the precipitate. This process was repeated several times until the pH of the supernatant after centrifugation was measured to be 7 using pH paper. The resulting MXene sample was dried in a vacuum oven at 65 °C and then stored in a dark, oxygen-free environment.

[0063] 2. Preparation of Ti3C2@TiO2

[0064] 200mg Ti3C2T x Add 0.2M NaBF4 to 30mL of 1.0M HCl. After mixing and stirring the solution for 30min, transfer it to a 100mL stainless steel autoclave lined with polytetrafluoroethylene and hydrothermally heat it at 160℃ for 12h. After naturally cooling to room temperature, centrifuge, wash several times with deionized water, and dry in a vacuum drying oven at 60℃ for 12h.

[0065] 3. Preparation of sulfonated polyetheretherketone cation exchange solution

[0066] 4g of peek was dried under vacuum at 100℃ for 24 hours. The dried sample was then dissolved in 100mL (80-150mL) of concentrated sulfuric acid and stirred at 60℃ (50-70℃) for 5-8 hours until completely dissolved. The reaction was then stopped, and the product was slowly poured into 500mL of prepared ice water while stirring. A white flocculent product was obtained. The product was washed with deionized water until the pH was approximately 7. The product was then dried under vacuum at 100℃ (60-100℃) for 24 hours (24-36 hours) to obtain sulfonated polyether ether ketone. 1g of sulfonated polyether ether ketone was dissolved in 10mL of LDM to prepare a 10wt% solution.

[0067] 4. Preparation of bipolar films

[0068] Cut the purchased anion exchange membrane into 4cm x 4cm squares and thoroughly wet the base membrane. Place the anion exchange membrane on a membrane holder and dry the membrane. Load 1 mL of 0.30 g / L catalyst onto the base membrane (3.14 cm²) using an impregnation method. 2 As an intermediate layer, it is dried at 60℃ for 1 hour; on the side impregnated with the intermediate layer catalyst, a cation exchange film solution is cast and left to dry overnight under natural conditions to form a film. The next day, it is crosslinked at 80℃ for 2 hours and then at 100℃ for 1 hour. After complete drying, the prepared bipolar film is immersed in a 0.5 mol / L NaCl solution for 24 hours.

[0069] Comparative Example 1

[0070] The only difference between this comparative example and Example 1 is that a catalytic intermediate layer is not used.

[0071] Comparative Example 2

[0072] The only difference between this comparative example and Example 1 is that the Ti3C2 catalytic intermediate layer is replaced with the Ti3C2@TiO2 catalytic intermediate layer.

[0073] Comparative Example 3

[0074] The only difference between this comparative example and Example 1 is that a TiO2 catalytic interlayer is used instead of a Ti3C2@TiO2 catalytic interlayer.

[0075] Performance Test 1

[0076] This performance test used a self-made four-stage glass apparatus to conduct current-voltage curve testing. The effective area of ​​the glass apparatus was 3.14 cm². 2 Two platinum sheet electrodes, serving as the positive and negative terminals of the power supply, are connected to a DC power meter to provide current. Two silver chloride reference electrodes are connected to a multimeter to test the transmembrane voltage of the bipolar membrane. The electrode chamber uses a 1.0 mol / L Na₂SO₄ aqueous solution, and the acid-base chamber uses a 1.0 mol / L NaCl aqueous solution. The electrode chamber and the acid-base chamber are separated by two Nafion 212 commercial ion exchange membranes, with the bipolar membrane to be tested inserted in between to separate the electrolytes in the acid and base chambers. The current density is linearly increased during the test, with an adjustable range of 0-300 mA / cm². 2 Record the transmembrane voltage of the bipolar membrane under different current densities.

[0077] Please see Figure 4 , Figure 4 (a)(b) Comparison of the electrochemical performance of the blank bipolar membrane, pure Ti3C2, pure TiO2, and Ti3C2@TiO2-0.25 modified bipolar membrane: the blank bipolar membrane has the highest transmembrane voltage, while the Ti3C2@TiO2-0.25 modified bipolar membrane has the best voltage drop. (At 100 mA·cm⁻¹) -2 Taking current density as an example, the transmembrane voltage of the blank bipolar membrane is 2.79V, while that of the Ti3C2@TiO2-0.25 modified bipolar membrane is only 1.75V, a reduction of 37.3%. Simultaneously, the water dissociation initiation voltage of this modified membrane is only 0.85V, a decrease of 13.3% compared to the blank membrane's 0.98V. This is because the Ti3C2@TiO2 composite catalyst possesses excellent interlayer conductivity, which can enhance the electric field strength in the interfacial ion dissipation region, significantly increasing the water dissociation rate.

[0078] Figure 4 (c) and (d) show the IV curves of the Ti3C2@TiO2 modified bipolar membranes with different impregnation concentrations: With increasing catalyst loading, the number of water dissociation active sites increases, water dissociation efficiency improves, and the overall transmembrane voltage decreases. (100 mA·cm) -2 Under the specified conditions, the transmembrane voltages of the modified bipolar membranes Ti3C2@TiO2-0.1, Ti3C2@TiO2-0.2, Ti3C2@TiO2-0.25, and Ti3C2@TiO2-0.3 were 2.39V, 2.15V, 1.75V, and 2.05V, respectively, with voltage drops of 14.3% to 37.3% relative to the blank membrane (2.79V). Among them, the bipolar membrane exhibited the best water dissociation performance when the catalyst concentration was 0.25g / L.

[0079] Performance Test 2

[0080] This performance test uses the same four-compartment electrolysis apparatus as the IV curve test. The long-term operational stability of the bipolar membrane is evaluated by the change trend of the transmembrane voltage over time under constant current conditions. The test current density is fixed at 100 mA / cm². 2 The voltage test interval was 15 minutes, and the total test time was set to 6 hours.

[0081] Depend on Figure 5 (b) The stability curves show that during the 6-hour constant current operation, the transmembrane voltage of the blank bipolar membrane without a catalytic intermediate layer continuously increases, with an average rise rate of 44.5 mV·h. -1 The transmembrane voltage of the modified bipolar membrane with a Ti3C2@TiO2 catalytic interlayer remained stable throughout, without a significant upward trend. This phenomenon demonstrates that the composite catalytic layer formed by in-situ growth of TiO2 on the Ti3C2 surface can be firmly anchored at the membrane interface, effectively mitigating catalyst leakage and detachment issues and ensuring stable water dissociation efficiency of the bipolar membrane during long-term operation. In summary, the Ti3C2@TiO2 interfacial catalytic layer not only optimizes the water dissociation performance of the bipolar membrane but also significantly improves the long-term operational stability of the membrane.

Claims

1. A method for preparing a bipolar film containing a Ti3C2@TiO2 catalytic interlayer, characterized in that, Includes the following steps: Ti3C2T x Sodium fluoroborate and hydrochloric acid undergo a hydrothermal reaction at 150~170℃ to obtain Ti3C2@TiO2; Ti3C2@TiO2 is loaded onto an anion exchange base membrane as a carrier and dried to form a Ti3C2@TiO2 catalytic intermediate layer; a cation exchange precursor membrane is formed by casting a cation exchange membrane onto the surface of the Ti3C2@TiO2 catalytic intermediate layer.

2. The method for preparing a bipolar film containing a Ti3C2@TiO2 catalytic interlayer according to claim 1, characterized in that, The Ti3C2T x The preparation method includes the following steps: treating titanium aluminum carbide with lithium fluoride-hydrochloric acid etching to obtain Ti3C2T. x .

3. The method for preparing a bipolar film containing a Ti3C2@TiO2 catalytic interlayer according to claim 1, characterized in that, After forming the cation exchange precursor membrane, it is cross-linked and cured in stages at high temperature: the first stage cross-linking temperature is 70-90℃, the second stage cross-linking temperature is 90-110℃, and after the cross-linking is completed, a composite bipolar membrane semi-finished product is obtained.

4. The method for preparing a bipolar film containing a Ti3C2@TiO2 catalytic interlayer according to claim 3, characterized in that, It also includes immersing the composite bipolar membrane semi-finished product in a 0.2~0.8 mol / L NaCl solution for activation treatment to obtain the bipolar membrane.

5. The method for preparing a bipolar film containing a Ti3C2@TiO2 catalytic interlayer according to claim 1, characterized in that, The raw material ratio in step S1 is: 180-220 mg Ti3C2T per x The powder corresponds to 25–35 mL of a mixture of 0.8–1.2 mol / L hydrochloric acid containing 0.15–0.25 mol / L sodium fluoroborate.

6. The method for preparing a bipolar film containing a Ti3C2@TiO2 catalytic interlayer according to claim 1, characterized in that, The cation casting solution is an organic solution of sulfonated polyether ether ketone, wherein the solid content of sulfonated polyether ether ketone is 8~12wt%.

7. The method for preparing a bipolar film containing a Ti3C2@TiO2 catalytic interlayer according to claim 6, characterized in that, The preparation process of sulfonated polyether ether ketone is as follows: polyether ether ketone is dissolved in concentrated sulfuric acid for sulfonation reaction; after the reaction is completed, the mixture is poured into ice water to quench and terminate the reaction, and a white flocculent crude sulfonated polyether ether ketone product is precipitated; the crude sulfonated polyether ether ketone product is washed with deionized water and vacuum dried to obtain sulfonated polyether ether ketone.

8. The method for preparing a bipolar film containing a Ti3C2@TiO2 catalytic interlayer according to claim 1, characterized in that, Includes the following steps: Ti3C2@TiO2 was loaded onto the surface of anion exchange base membrane using an impregnation method.

9. A bipolar membrane containing a Ti3C2@TiO2 catalytic interlayer, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 8.

10. The application of the bipolar membrane containing a Ti3C2@TiO2 catalytic intermediate layer as described in claim 9 in electrodialysis.